2014
DOI: 10.3758/s13414-014-0730-3
|View full text |Cite
|
Sign up to set email alerts
|

“Just do it when you get a chance”: the effects of a background task on primary task performance

Abstract: Two experiments investigated multitasking performance with a new "prioritized-processing paradigm" in which participants responded only to a high-priority primary task when this task required some action, responding to a low-priority background task only when no action was required for the primary task. In both experiments, performance was worse on the primary task than on the same task performed in isolation, indicating that this attempt to give absolute priority to the primary task is not sufficient to prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 56 publications
6
56
1
Order By: Relevance
“…Closer relatives to our own design are dual-task studies (with two distinct stimuli for each task) involving a go/nogo task as Task 2. For example, Miller (2006) showed that trials involving a no-go stimulus (vs. a go stimulus) in Task 2 were characterized by a Task 1 RT increase (see also Janczyk & Huestegge, 2017;Miller & Durst, 2014, 2015. It was assumed that this effect is based on an inhibitory response triggered by the no-go stimulus, which (either directly or via its transformation into a dedicated Binhibitory response^selection process) eventually prolongs Task 1 processing (see Röttger & Haider, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Closer relatives to our own design are dual-task studies (with two distinct stimuli for each task) involving a go/nogo task as Task 2. For example, Miller (2006) showed that trials involving a no-go stimulus (vs. a go stimulus) in Task 2 were characterized by a Task 1 RT increase (see also Janczyk & Huestegge, 2017;Miller & Durst, 2014, 2015. It was assumed that this effect is based on an inhibitory response triggered by the no-go stimulus, which (either directly or via its transformation into a dedicated Binhibitory response^selection process) eventually prolongs Task 1 processing (see Röttger & Haider, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While this might basically be the case (since costs might be relatively low and are therefore tolerable), this claim is certainly a bit exaggerated, given recent work where these costs are measured more explicitly (cf. Miller & Durst, 2014. Hence, we have to tackle the issue of what effectively is manipulated by having an effort-instruction trials mixed into a design with standard trials.…”
Section: It Becomes Evident Frommentioning
confidence: 99%
“…Another set of studies in which a no-go BCE was assessed used a variant of the PRP paradigm, known as the prioritized-processing (PP) paradigm (Miller & Durst, 2014. In this variant, both Task 1 and Task 2 are choice/no-go tasks (i.e., two go responses are possible).…”
Section: A Closer Look At the No-go Bcementioning
confidence: 99%
“…In Experiment 1 of Miller and Durst (2014), participants gave both responses with either the left or the right index finger, and the fastest RT1s were observed in R1-R2 compatible trials, intermediate RT1s in R1-R2 incompatible trials, and the slowest RT1s if Task 2 was a no-go trial (even though none of these possible R2s actually had to be carried out). 1 The results revealed both an R1-R2 and a no-go BCE in this experiment, and similarly so in Experiments 1 and 2 of Miller and Durst (2015).…”
Section: A Closer Look At the No-go Bcementioning
confidence: 99%